Práticas de desempoderamento docente no cotidiano da escola de educação fundamental - Bolson, Janaina Boniatti (Universidade do Vale do Rio dos Sinos, 2011)
The dissertation has as object of study teacher disempowerment practices at contemporary schools. Based on theoretical ideas of Contreras, Foucault, Nóvoa, Tardif, Lugli and Vicentini, the study had as goals: a) identify how the teacher disempowerment practices work in the daily school events and investigate how those practices are understood by the teachers; b) analyze how those practices are being incorporated to the school environment. The investigation that originated this dissertation was developed through a qualitative approach, in which nine working teachers from public schools with different teaching times were interviewed through the semi-structured interview technique. The analysis was developed among five main issues – 1) teaching knowledge and professional competence; 2) pedagogical meetings and teacher action; 3) school environment and teacher valuation; 4) evaluative processes and teaching; 5) teacher autonomy – which indicate evidences of that disempowerment process that nowadays teachers are suffering from and show evidences that teachers are working individually and not much cooperatively, what indicates that changes on the way of these professionals organization are needed. As contributions to consider in the teacher training area, intentions of resistance from teachers as a group for the retrieval of autonomy and teacher power inherent to their professional practice have been outlined. Finally, some challenges that need to be faced by the teachers as a group and as social responsible for teaching are pointed, like the need of establishing with the society the disclosure of respect for the teaching job, so then a valuation and acknowledgement movement can be introduced to the daily school environment.
Keywords: School environment; Teacher autonomy; Teacher power; Teaching training; Cotidiano escolar; Autonomia docente; Poder docente; Formação de professores; ACCNPQ::Ciências Humanas::Educação